Timely health care seeking and first source of care for acute febrile illness in children in Hawassa, southern Ethiopia - Shimelis, T; Schierhout, G; Tadesse, BT; Dittrich, S; Crump, JA; Kaldor, JM; Vaz Nery, S (Public Library of Science, 2022)
Background Timely health care seeking with access to quality health care are crucial to improve child survival. We conducted a study which aimed to identify factors influencing timely health care seeking and choice of first source of health care in Ethiopia. Methods A total of 535 caregivers who sought health care for febrile children aged under 5 years at a tertiary hospital, and one urban and two rural health centres in Hawassa, southern Ethiopia were recruited to participate in the study from August to November 2019. Caregivers were interviewed using pretested structured questionnaires on socio-demographic and clinical factors to identify associations with health care seeking practice and first source of care, and reasons for particular practices. Delayed care seeking was defined as seeking care from a health facility after 24 hours of onset of fever. Results Of 535 caregivers who participated, 271 (50.7%) had sought timely health care; 400 (74.8%) utilized a primary health care (PHC) facility as first source; and 282 (52.7%) bypassed the nearest PHC facility. Rural residents (adjusted odds ratio (AOR) 1.85; 95% CI 1.11–3.09), and those who reported cough (AOR 1.87; 95% CI 1.20–2.93) as a reason for consultation were more likely to delay seeking health care. While caregivers were less likely delayed for children aged 24–35 months (AOR 0.50; 95% CI 0.28–0.87) compared to infants. Utilizing higher-level hospitals as the first source of care was less frequent among rural residents (AOR 0.15; 95% CI 0.06–0.39) and in those with no formal education (AOR 0.03; 95% CI 0.01–0.27). Those having a longer travel time to the provider (AOR 2.11; 95% CI 1.09–4.08) more likely utilized higher hospitals. Conclusion We identified a need to improve timely health seeking among rural residents, infants, and those presenting with respiratory symptoms. Improvements may be achieved by educating communities on the need of early care seeking, and ensuring the communities members’ expectations of services at each level consistent with the services capacity.